Automatic construction of restriction site maps. - Pearson, W R (1982)
A computer program is described which constructs maps of restriction endonuclease cleavage sites in DNA molecules, given only the fragment lengths. The program utilizes fragment length data from single and double restriction enzyme digests to generate maps for linear or circular molecules. The search for a map can be limited to the unknown (insert) region of a recombinant phage or plasmid. Typical restriction maps with four or five enzymes which cut at three to five unknown sites can be calculated in a few minutes.